Mechanics of Materials - Formulas and Problems Engineering Mechanics 2 - Gross, Dietmar; Ehlers, Wolfgang; Wriggers, Peter; Schröder, Jörg.; Müller, Ralf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book contains the most important formulas and more than 140 completely solved problems from Mechanics of Materials and Hydrostatics. It provides engineering students material to improve their skills and helps to gain experience in solving engineering problems. Particular emphasis is placed on finding the solution path and formulating the basic equations. Topics include: - Stress - Strain - Hooke's Law - Tension and Compression in Bars - Bending of Beams - Torsion - Energy Methods - Buckling of Bars - Hydrostatics     .
Preface -- Literature, Notation -- 1. Stress, Strain, Hooke's Law.- 2. Tension and Compression in Bars.- 3. Bending of Beams.- 4. Torsion.- 5. Energy Methods.- 6. Buckling of Bars.- 7. Hydrostatics.    .
Keywords: Mechanical engineering; Civil engineering; Electrical engineering; Mathematical physics; Mechanical Engineering; Civil Engineering; Electrical and Electronic Engineering; Theoretical, Mathematical and Computational Physics